Feminist Literary Criticism Meets Feminist Theology: Yashodhara and the Rise of Hagiographical Fiction in Modern Feminist Re-visioning - Soni Wadhwa (SAGE Publishing, 2021)
Feminist re-visioning has led to heterogenous retellings of mythological heroines in fiction. Sita and Draupadi, two of the well-known Indian mythological characters, have been explored in various capacities in mythological fiction. Yashodhara, Buddha’s wife, is a recent addition to this re-visioning project. This article seeks to engage with three retellings of Yashodhara’s story—each of which is radically different from the others. The result is the rise of hagiographical fiction around the character—responsive to the Buddhist ethos of love and spirituality. This article argues that the most intriguing representations of Yashodhara found in this fiction are rooted in the nonoppositional agency given to her character.